Nuclear matter within a dilatation-invariant parity doublet model: The role of the tetraquark at nonzero density - Gallas, Susanna; Giacosa, Francesco; Pagliara, Giuseppe (Nuclear physics. A, Nuclear and hadronic physics, 2011)
We investigate the role of a scalar tetraquark state for the description of nuclear matter within the parity doublet model in the mirror assignment. In the dilatation-invariant version of the model a nucleon-nucleon interaction term mediated by the lightest scalar tetraquark field naturally emerges. At nonzero density one has, beyond the usual chiral condensate, also a tetraquark condensate. The behavior of both condensates and the restoration of chiral symmetry at high density are studied. It is shown that this additional scalar degree of freedom affects non-negligibly the properties of the medium.
Gesehen am 13.07.2023